Democracy and publicity - Parr, Tom (Pontificia Universidad Católica del Perú. Fondo Editorial, 2024)
In what follows, I will defend neither the idea that democracy is valuable (in part) because of the collective achievement that it facilitates, nor the idea that alternative systems of government fare less well in this regard. In part, this is because I take the truth of these claims to be largely self-evident, at least once we suitably unpack their precise content. And in part, this is because others have discussed these views, and I have little more to add (Rawls, 2000, pp. 201-206)1. Instead, my principal aim is to contend that this justification for democracy gives us reason to constrain the kinds of moral demands that individuals may place on each other. More specifically, I shall argue that, if democracy is valuable (in part) because of the collective achievement that it facilitates, then we have reasons to allow individuals to make demands on each other only if those demands pass the test of publicity. Exactly what this means, and why it is the case, are issues to which we shall now turn.
Keywords: Publicidad; Democracia; https://purl.org/pe-repo/ocde/ford#6.02.00